ORGANIZATIONAL CHANGE MANAGEMENT IN HIGHER EDUCATION: A RESPONSE TO THE DYNAMICS OF NATIONAL EDUCATION POLICY - Abdul Majir; Robertus Hudin (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
The dynamics of national education policies encourage universities to make sustainable adaptations through organizational changes. As organizations with complex structures and cultures, universities face significant challenges in translating policy demands into effective institutional practices. This study aims to analyze the implementation of Organizational Change Management (OCM) in higher education as a response to the dynamics of national education policies. This study uses a qualitative case study design. Data was collected through in-depth interviews, analysis of policy documents, and observation of the process of implementing changes, involving institutional leaders, lecturers, and education staff. The study's results show that organizational changes in higher education occur across structural, procedural, and cultural dimensions. Leadership and communication play an important role in driving policy implementation, while limited stakeholder participation and organizational resources can trigger passive resistance. In addition, national education policies have a dual impact: they encourage improvements in academic governance and innovation, but they also pose challenges in their implementation. The findings of this study confirm that the success of policy-driven organizational change depends heavily on the effectiveness of systematic, participatory, and sustainable change management. This research makes a theoretical contribution to the study of OCM in higher education and has practical implications for university leaders and policymakers.